2015
DOI: 10.1007/s00423-015-1338-3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal drainage after liver transplantation from deceased donors

Abstract: Equal results can be achieved with or without an abdominal drain in recipients with whole-liver grafts in spite of an increased risk of postoperative infection and biliary leakage in the former group. A benefit of AD as a diagnostic tool could not be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Schwarz and colleagues found a higher incidence of bile leak in the drainage group, with half of them identified early through the drain. This study also showed more infectious complications when drains were used 3 . It was suggested by Weiss and colleagues not to use open‐circuit drains, as these drains were associated with significantly more intra‐abdominal infections 4 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Schwarz and colleagues found a higher incidence of bile leak in the drainage group, with half of them identified early through the drain. This study also showed more infectious complications when drains were used 3 . It was suggested by Weiss and colleagues not to use open‐circuit drains, as these drains were associated with significantly more intra‐abdominal infections 4 .…”
Section: Discussionsupporting
confidence: 55%
“…Higher incidence of infections in the drainage group was reported by Schwarz et al Only Schwarz et al reported a greater incidence of infections in the drainage group (63.8% vs. 39.7%; p = .015), without differences in the other two studies. 3 Weiss and colleagues compared open-circuit (Easy-Flow) and closed-circuit (Robinson) drains and found significantly more intra-abdominal infections when open-circuit drains were used (50% vs. 22.5%; p < .001). 4…”
Section: Systematic Review Of the Literature On Outcomes Related To T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to isolated LTx, single institution studies reported no benefits of drain insertion in overall morbidity and mortality (21)(22)(23)(24). However, the only systematic review reported on this theme in 2011 did not find any evidence to conclude whether routine abdominal drainage is useful or harmful in patients undergoing LTx (25).…”
Section: Discussionmentioning
confidence: 99%
“…While reports in the literature regarding the potential benefit of prophylactic surgical drainage are rather sporadic and show contrasting results as to whether there is any advantage of inserting drains after isolated liver and kidney transplantation (8,(21)(22)(23)(24)(25)(26)(27)(28)(29), there is currently no study that has addressed this topic in combined liver and kidney transplantation (CLKTx).…”
Section: Introductionmentioning
confidence: 99%